DIVERSITY, OCCURRENCE AND ABUNDANCE OF ODONATES OF TUNGA RIVER BANK, ADJOINING FIELDS AND CULTIVATED LANDS IN SHIVAMOGGA DISTRICT OF KARNATAKA, INDIA. - NAIK KL; SAYESWARA HA (Innovare Journal of Sciences, 2017)
ABSTRACT Objective: The major objective of this study was to find out the diversity, occurrence and abundance odonates of Shivamogga at two localities viz. Tunga river bank, adjoining fields and cultivated lands Methods: Odonates were sampled for a period of five months from July to November 2016. Field observations were made once in a week. Odonates were observed, captured, identified and released immediately at the spot of capture. The Odonates which were difficult to identify in the field were collected as voucher specimens using a hand net. The dead specimens were kept in insect collection box. Odonates were identified by using field guides and hand book of common odonates of central India. Results: A total of 29 species of odonates belonging to 7 families and 24 genera were recorded from the study area. 14 species of dragonflies and 15 species of damselflies were recorded and identified. 13 species of dragonflies sighted in the family Libellulidae, while Aeshnidae was represented by a single species.Â  Nine species of damselflies sighted in family Coenagrionidae. Family Chlorocyphidae was represented by three species, while Platycnemididae, Lestidae and Calopterygidae were represented by single species each. Conclusion: The present investigation shows that, the study area host a number of odonates. Due to different anthropogenic activities the odonates diversity is in declining mode. This study would serve as a frame of reference for future initiatives in studying odonates diversity. Keywords: Odonates, dragonflies, damselflies, Shivamogga, Karnataka